Consideraciones sobre la organización de los servicios hospitalarios ante una epidemia de Influenza A (H1N1). Experiencia en Cienfuegos 2009 - Grupo operativo provincial de atención médica a los enfermos adultos hospitalizados (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2011)
Introduction: The organization of the hospital services to face an epidemic of Influenza A (H1N1), a condition of respiratory transmission, constitutes a challenge and the success will depend, to a great extend, of the organizational changes implemented from the stage of planning, as they are an indispensable part of the strategy work. Objective: To describe the main organizational experiences that were developed in the Cienfuegos's Provincial Hospital Dr. Gustavo Aldereguía Lima, during the year 2009 to face the A (H1N1) pandemic influenza. Method: A prospective study. Investigation in systems and services of the health system, where a wide bibliographical revision was made, combined with group's techniques (for the progressive definition of the organizational strategy) and the experiences contained in the "portfolio of decisions" created for that purpose. Results: Different changes have been recognized, such as the modification of the habitual flows and concepts in the medical attention, included the extension and expansion of the services and the beds' assignation. It was considered logic the reduction of the elective surgical activity, working in teams, the materialization of differentiated consultations in emergency services, the definition of an area for care to severe patients, as well as a priority in the management of the pregnant and postpartum women and newborns. We kept too the continuous training of the medical personnel and their protection, the isolation of cases, the feeding and sterilization. Conclusions: The reorganization of the medical care, the continuous qualification of the professional staff, the adequate infraestructure, the optimization of the resources, management and team work are key points in the organization for a successful confrontation of an epidemic.